EFEKTIFITAS METODE DEMONTRASI DALAM PEMBELAJARAN FIQIH - Sy. Rohana Sy. Rohana (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2019)
Given the importance of increasing the effectiveness of the method in the learning process and achieving good learning outcomes, the teaching and learning process requires a method that supports or becomes a benchmark so that educational goals can be achieved in accordance with what was planned. In this article, the writer illustrates that effectiveness is an activity that can produce business results, because the achievement of the goals of an ideal and efficient achievement is reached, so that the effect is declared successful and can be measured to bring satisfying results. The effectiveness of fiqh learning to students through learning activitiesoriented to life skills, fiqh learning activities that are packaged so that students get learning experiences from the results of their learning. This learning activity can stimulate positive emotions in students, so that the effectiveness of learning can be achieved optimally. Demonstration method is a teaching method that uses demonstration to clarify an understanding or to show how to do something for students. The writer meant by learning fiqh in the discussion of this article is an attempt to transfer the science of jurisprudence to Islamic laws by the teacher to students - students using the demonstration method.